2007
DOI: 10.1007/s10096-007-0396-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among commensal isolates of Escherichia coli and Staphylococcus aureus in the Indonesian population inside and outside hospitals

Abstract: The prevalence of antimicrobial resistance among the commensal microflora was examined in the Indonesian population inside and outside hospitals. A total of 3,995 individuals were screened in two major urban centers. Among Escherichia coli from rectal samples (n = 3,284) the prevalence of resistance to ciprofloxacin and other classes of antibiotics was remarkably high, especially in individuals at the time of discharge from hospital. Staphylococcus aureus isolates (n = 361) were often resistant to tetracycline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 35 publications
2
43
0
5
Order By: Relevance
“…The MDRI of some of the isolates (33.00%) is well above 20% which signifies that the bacteria are highly resistant to available antibiotics. Multidrug resistance among E. coli isolates has been subjects of concern worldwide (Chitnis et al, 2003;Lestari et al, 2008). Dissemination of resistance genes among isolates have been held responsible for rapid and widespread multidrug resistance among not only E. coli, but numerous other pathogenic bacteria as well.…”
Section: Discussionmentioning
confidence: 99%
“…The MDRI of some of the isolates (33.00%) is well above 20% which signifies that the bacteria are highly resistant to available antibiotics. Multidrug resistance among E. coli isolates has been subjects of concern worldwide (Chitnis et al, 2003;Lestari et al, 2008). Dissemination of resistance genes among isolates have been held responsible for rapid and widespread multidrug resistance among not only E. coli, but numerous other pathogenic bacteria as well.…”
Section: Discussionmentioning
confidence: 99%
“…21 In this study, we aimed to gain more insight in the more recent epidemiology of MRSA and S. aureus harboring the pvl genes in the Indonesian hospital setting to develop targeted preventive measures. Similar to the study described by Lestari and others, 19 we performed a multicenter study focused on patients at discharge. Molecular characterization of S. aureus isolates was carried out and possible risk factors for colonization among these patients were analyzed.…”
Section: Introductionmentioning
confidence: 96%
“…Severin and others reported that among 98 S. aureus isolates from 999 patients screened at discharge in [2001][2002] in two cities on the island of Java (Semarang and Surabaya), only two strains were identified as MRSA (carriage rate 0.2%). 19,20 Among 263 isolates from healthy persons, patients in the community, and patients at the time of admission to the hospital, not a single MRSA was found. However, an unexpectedly high prevalence of PantonValentine leukocidin (PVL) genes among methicillin-sensitive S. aureus (MSSA) was documented among both patients and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the predominant multi-resistant bacteria that causes the infection such as P. aeruginosa, Klebsiella pneumoniae, Escherichia coli and methicillin resistant Staphylococcus aureus (S. aureus) (MRSA) have been found in several hospitals in Indonesia [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%